Predicting the Quality of Life Based on Health-promoting and Mindfulness Lifestyle in Pregnant Women With Obesity Referring to Comprehensive Health Centers in Arak City, Iran - Effat Noroozi; Akram Dehghani; Mostafa Nokani; Seyyed Abbas Haghayegh (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Obesity is one of the complications focused on by the health systems worldwide, and its social, psychological, and economic outcomes led it to be considered an epidemic and global threat to health. Objectives: The present study aimed at predicting the quality of life (QoL), based on health-promoting and mindfulness lifestyle in pregnant women with obesity, referring to comprehensive health centers in Arak, Iran. Methods: The present descriptive-correlational study was performed on all pregnant women with obesity, referring to comprehensive health centers in Arak, as the statistical population, from July to September 2019, of which 200 subjects were selected by the stratified cluster sampling method, based on inclusion and exclusion criteria. The sample size was determined using the Hooman formula. Data collection instruments included the World Health Organization QoL questionnaire (2004), the health-promoting lifestyle profile by Walker et al. (1987), and the mindful attention awareness scale by Brown and Ryan (2003). The Pearson correlation matrix and multiple linear regression test were used for data analysis using SPSS version 24; P-value was 0.05. Results:: The results showed that the variables of health-promoting lifestyle (i e, nutrition 30.07±6.57, exercise 36.46±7.36, responsibility 23.21±4.80, stress management 3.63±16.26, interpersonal relationships 13.68±4.98, spiritual growth 18.69±3.31, and mindfulness 65.09±11.93) could explain QoL (92.28±13.52) in pregnant women with obesity (P<0.05).Conclusion: The findings support the contribution of underlying psychological mechanisms to QoL. Therefore, considering these variables in preventive measures and designing more effective treatments can help researchers and therapists.